Biofunctional coatings for 3D-printed bone scaffolds: A comparative study on polydopamine-assisted bioactive ceramic coatings - MinJoo Kim; Qaisar Nawaz; Bastian Hartmann; Pedro Henrique da Rosa Braun; Constanze Eulenkamp; Jan Torgersen; Hauke Clausen-Schaumann; Aldo Roberto Boccaccini; Boris Michael Holzapfel; Susanne Mayer-Wagner (Chemical Engineering Journal, 2026)

Surface temperature changes indicate disease onset after pulmonary murine corona virus infection, but do not constitute a humane endpoint - Rebecca Nistelberger; Patrizia Gibler; Thomas Filip; Manuel Salzmann; Boris Hartmann; Bruno K. Podesser; Roberto Plasenzotti; Philipp J. Hohensinner; Julia B. Kral-Pointner (Veterinary Research Communications, 2025)
Mouse models are important contributors for understanding the immune system during infections. Objective parameters help to assess the course of infection and guarantee animal welfare. In this study we analyzed if surface temperature measured via thermal imaging of the dorsal area is a suitable marker to evaluate animal wellbeing during murine coronavirus (MCoV) infection. Infected BALB/c mice displayed severe symptoms whereas C57BL/6 mice were less affected. In BALB/c animals, temperature increased from 27.1 °C to 28.4 °C within 24 h with levels remaining slightly elevated over the observation period. In contrast, a decrease in body weight was consistent through the period with 60% of the animals reaching the previously set termination point of 20% weight loss ( n = 6). Also, C57BL/6J animals showed a significant temperature increase from 27.1 °C to 28.4 °C within 24 h and a significant weight loss over time with two out of ten reached weight loss end point. However, temperature and weight changes were not related in individual animals. In contrast to temperature values, body weight clearly set a trajectory towards early termination. Taken together, our data indicate that superficial temperature did not serve as a predictive parameter for defining humane end points, but indicate disease onset after pulmonary virus infection.